Thermal conductivity of composite materials: Alkali carbonate-based melts filled with fine α-Al2O3. (April 2018) - Dokutovich, Vasiliy N.; Khokhlov, Vladimir A.; Zakir'yanova, Irina D.
Graphical abstract: Highlights: The thermal conductivity (λ) of molten salt-Al2 O3 composites is first measured. The thermal conductivity grows as the temperature and α-Al2 O3 concentration rise. The temperature coefficient dλ/dT decreases sharply as the oxide content increases. A correlation between the λ and the mean thickness of the molten salt gap is found. A model is proposed for describing the heat transfer in the composites under study. Abstract: The thermal conductivity of composite materials, specifically alkali carbonate-based melts filled with fine α-Al2 O3, was measured in relation to the temperature and thickening agent content using the steady-state coaxial cylinder method. The thermal conductivity was found to be a linear function of the temperature in the range from 670 K to 930 K for salt melts and all of the thickened melt-oxide mixtures that were studied, while this value increased non-linearly as the α-Al2 O3 volume fraction increased showing a tendency to be unchanged at α-Al2 O3 volume concentrations greater than 15%. The thermal conductivity of the (Li2 CO3 - Na2 CO3 - K2 CO3 )eut + α-Al2 O3 composites measured was adequately described by the Maxwell-Wagner equations derived for two-phase heterogeneous materials. The alternating sign of the temperature coefficients of the composites thermal conductivity and peculiarities of its concentration dependency point to the existence of "ionic heat conductor - oxide heat insulator" transaction in alkali carbonate-based melts thickened with fine α-Al2 O3 .